Shaykh Zayn al-Abidin bin Muhammad al-Fatani's discourse on eschatology - Ghafirah Idris (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study aims to explore and analyze Shaykh Zayn al-'Abidin bin Muhammad al-Fatani's thoughts on eschatology based on his prominent works on 'aqidah. Details of Shaykh Zayn al-'Abidin al-Fatani's thoughts on this topic need to be studied thoroughly especially in the present-day Islamic discourse, where there are attempts to challenge the truth of eschatological matters. The method used in this study is library research, within which textual analysis of Shaykh Zayn al-'Abidin al-Fatani's main works is applied. The findings indicate that this study has completed the gap of other researches where there are no study carried out on Shaykh Zayn al-'Abidin al-Fatani's views on eschatology. The findings also demonstrate that Shaykh Zayn al-'Abidin al-Fatani successfully discusses most of the topics related to eschatology in his writings beginning from the death of man until his final destination in the Hereafter. In addition to that, Shaykh Zayn al-'Abidin al-Fatani plays a great role in transmitting the teaching of the AshÑarites to the Malay society which determines the theological structure of the Malay region since his discourse on eschatology is based on the AshÑarites point of view. Shaykh Zayn al-'Abidin al-Fatani also does not overlook the challenges mounted against the eschatological matters such as the denial of the punishment of the grave and resurrection of the body as well as the denial of the beatific vision of God (ru'yat Allah). He, as other Malay Muslim scholars affirm the possibility of those events. As far as the Malays are concerned, his discourse on eschatology is a notable intellectual heritage in understanding the real condition of the Malays in order to remind them of their real objectives and responsibilities in this life as well as to create awareness within themselves that this world is only a temporal destination in order to gain real happiness in the afterlife.